Influencing Factors Customer's Interest In Transaction The Mudharabah Savings Product The Syariah Banking Sambas Regency (Study On Iais Sambas Employees) - Muslimin; Munadi; Wulan Purnamasari (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2023)
The purpose of this study to determine the income that affects the interest of employees IAIS Sambas transact and use Islamic banking services in Sambas. To determine the influence of banking services IAIS Sambas employees in using Islamic banking services Sambas regency. To determine the religious level of IAIS Sambas employees in using Islamic banking services in Sambas. To determine the significant effect of variables X1, X2, X3 on variable Y in Mudharabah savings products in Islamic Banking Sambas regency. The method used in this study is the type of research used in this study is a field study using a quantitative approach. The data collection is done by research that will be conducted using indirect observation techniques because it only uses questionnaires (questionnaires) as material for data retrieval. The source of data in this study is the employees of IAIS Sambas amounting to p as many as 140 employees. The data analysis techniques in this study descriptive analysis, test research instruments, Partially, variable Islamic banking services (X1) has a value of t-count > t Table is equal to 2.419 > 1.659 and a GIS value of 0.008. Based on the hypothesis, H1 is accepted and H01 is rejected so that Sharia banking services partially affect the interest in saving. Employee income variable (X2) has a t-count value of 2.813 > 1.659 and a GIS value of 0, 043. Based on the hypothesis that H2 is accepted and h02 is rejected so that employee income partially affects the interest in saving. Employee religious variable (X3) has a t-count value of 2.380 > 1.659 and a GIS value of 0.006. Based on the hypothesis that H3 is accepted and h03 is rejected so that the employee's religion partially affects the interest in saving. In the F test (simultaneous), based on the results of the F test on the Anova table shows that the value of F is 3,232 with a probability value of 0,000 so < 0.05. Then f count > F table is 3,232 > 2,461 so that based on the hypothesis used in this study means h3 accepted and h03 rejected. Thus, employee income, Sharia banking services and employee religion simultaneously affect the interest in saving.